The Smoke of The Incense and The Roar of The Lion: Confucianism Under The Colonial Political System in Indonesia - Harto Juwono (Faculty of Cultural Sciences, Universitas Sebelas Maret, 2024)
This article aims to provide a brief overview regarding the existence of Confucianism as a religion in the Dutch East Indies and its relationship with the colonial ruling regime during the last four decades of Dutch rule. With the overview, it is hoped that the type of colonial policy that was made towards the Chinese ethnic belief could be understood, whether in social or political aspects and also its relevance to world developments that took place at the time. To realise this goal, the method used in this paper is the historical research method which consists of four stages: data search (heuristic), source criticism, interpretation, and reconstruction as a form of final academic presentation. With this method, it is hoped that a short paper can be presented that is arranged in a reconstructive manner and is able to provide answers to research problems. As a final conclusion, this paper reveals that in principle, colonial political interests cannot be separated from the existence of religion in her colony, including Confucianism. Especially the international aspect that began to colour the existence of this religion in the Dutch East Indies colony became the main motivation for the colonial government to determine their policies. In this case, the dualistic nature of Dutch colonial policy can be recognised.